Ouderling en Oud-Ouderling Sarel Cilliers - Strauss, Piet J. (HTS teologiese studies, 2020)
Sarel Cilliers as an elder or former elder in church: The well-known Voortrekker Sarel Cilliers was in the first place not recognised as a military or cultural leader, but a spiritual leader and respected elder in church. Apart from his emotional approach to the affairs of the Dutch Reformed Church of which he was a member in a congregation, Cilliers was a reformed member who strifed to obey the Bible, the Reformed confessions of faith and the so-called law of his church. Cilliers was chosen to take the lead when the Voortrekkers made a covenant with God before the Battle of Bloodriver in Natal on 16 December 1838. This covenant was initiated by the then leader of the Trekkers, Andries Pretorius. Cilliers did his work as an elder truthfully and with enthusiasm. He was strict and truthfull in his visits to church members and represented his congregation on major assemblies. In these assemblies fellow church members treated him with respect. Cilliers was an elder in a church which had to be settled in the interior of South Africa, often under abnormal circumstances. He sometimes had to do tasks of the minister of the congregation as well. Sarel Cilliers became known as a special elder in church.Contribution: This article gives an insight in the view and practice of the office of the elder in the Dutch Reformed Church in pioneer circumstances in the 19th century. It opens an assessment of this office for implementation in recent times. Apart from that the article sheds light on truthful understanding of the vow of Afrikaners at Blood River in 1838. This matter remains a point of discussion in recent times.